PERANCANGAN SISTEM INFORMASI PERSEDIAAN BARANG MENGGUNAKAN WATERFALL Studi Kasus: PT.Khatulistiwa Surya Nusa Jakarta - Noer Hikmah; Herlawati Herlawati; Nita Merlina (Paradigma, 2013)
In the information age business activities of an organization can not be separated from the role ofinformation systems and information technology, information system is a mainstay tool in order towin the competition in the industry. PT Khatulistiwa Suryanusa is a company engaged in theservice and special Parts for Sale Jeep. In the company's sales and purchase process is still donemanually. this causes various problems, including the management of data in the warehouse havedifficulty to control the stock of goods in and out. To overcome such problems, the author intendsto try to handle the processing of data on PT Khaulistiwa Suryanusa and design a systeminventory information. The data was collected by the method of literature review, interviews, andobservation method. Systems development method of information system using the waterfallmethod. whereas the method of data flow is used structured methods, DFD (Data Flow Diagram)describe the functional model and ERD (Entity Relationship Diagram) to describe the data model.The information system was built using Visual Basic software with database microsoft access.Keywords: system inventory information, Waterfall, ERD